The Effectiveness of Realistic Mathematics Approach Application to Improve Students' Mathematical Literacy - Yusmi, Annisa Nurul; Halimah, Andi; Nur, Fitriani (JTMT: Journal Tadris Matematika, 2024)
Mathematical literacy is an individual's ability to formulate, use, and interpret mathematics in various contexts. However, currently students in Indonesia have very low literacy skills. The aim of this research is to test the effectiveness of a realistic mathematics approach in improving students' mathematical literacy skills. This type of research is quasi-experimental using a Nonequivalent Control Group Design, involving 80 students as research samples. The instrument of this research is a test that is valid and reliable, and the data collected was analyzed using the N-Gain test and the Independent Sample t test. The results of this research show that in the experimental class the level of students' mathematical literacy ability was at level 4 at 62.5%, with an average value of students' mathematical literacy ability in the experimental class of 65.48, while in the control class the level of students' mathematical literacy ability was at level 4 it was 62.5%, with an average value of students' mathematical literacy skills in the experimental class of 65.48. So it was concluded that the realistic mathematics approach was effective in improving students' mathematical literacy skills, with the N-Gain Score achieved reaching 61% or quite effective.